The Role of International Coffee Organization (Ico) In Advancing EUDR Readiness for Sustainable “Coffee Belt” Industry - Nur Mujahadah Khoiriyah (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
Coffee, with around 125 known species, ranks among the most globally traded commodities and is a key source of foreign income for numerous developing nations. Its value chain is complex and highly exposed to economic and environmental risks, especially for smallholders. These challenges have intensified with the EU Deforestation-Free Regulation (EUDR) enacted in June 2023, which restricts imports of seven key deforestation-linked commodities, including coffee. This study aims to analyze the role of the International Coffee Organization (ICO) in advancing the readiness of coffee-producing countries, particularly in the Coffee Belt, for the implementation of the European Union Deforestation-Free Regulation (EUDR). This research adopts a descriptive qualitative method and utilizes both primary and secondary data, including official statements, reports, and meeting records, alongside sources obtained through library research. It explores the role of the International Coffee Organization (ICO) using Clive Archer’s (2001) conceptual framework, which viewed intergovernmental organizations (IGOs) as instruments, actors, and forums. The findings signify that the International Coffee Organization (ICO) plays a strategic role as a coordination instrument and source of information, an independent actor in policy advocacy, and a deliberate forum that brings together multiple stakeholders to support EUDR implementation.